Comparison of high efficiency flexible CdTe solar cells on different substrates at low temperature deposition. (1st December 2016) - Salavei, Andrei; Menossi, Daniele; Piccinelli, Fabio; Kumar, Arun; Mariotto, Gino; Barbato, Marco; Meneghini, Matteo; Meneghesso, Gaudenzio; Di Mare, Simone; Artegiani, Elisa; Romeo, Alessandro
Graphical abstract: Highlights: First time flexible CdTe solar cells by low substrate temperature on thin glass. First time comparison of flexible cells on different substrates. Polyimide substrates show lower transmittance and give more strain in the CdTe structure. Thin glass assures higher efficiencies and higher reliability. Abstract: In this paper we present for the first time flexible CdTe solar cells deposited on ultra-thin glass using a low temperature process and compared the results to CdTe cells deposited on polyimides. The effects of the different substrates on the morphology and crystal structure of CdTe absorber layers, as well as on the efficiency of solar cells were investigated by means of different characterization techniques. Atomic force microscopy measurements showed that the CdTe layers deposited on different substrates have a similar morphology. XRD analysis was used to study the structure and the orientation of the crystallite of the CdTe layers on the different substrates. Micro-Raman spectroscopy provided evidence of both the TO phonon of CdTe and the A1 phonon of Te, whose peak position is somehow dependent from the substrate material. CdCl2 treatments change the crystal orientation of the CdTe layers, with the loss of preferential orientation. In the case of the polyimide substrate it has been seen that its transparency decreases after CdCl2 activation treatment, resulting in a parasitic light absorbance and in lower photo-current values of the devices. Moreover strain of the CdTe surface is observed for cells deposited on polymers. Cells on ultra-thin glass do not show these issues, confirming the glass to be an interesting alternative substrate for flexible CdTe solar cells.